A randomised controlled trial comparing incentive spirometry with the Acapella® device for physiotherapy after thoracoscopic lung resection surgery1. (21st May 2014) - Cho, Y. J.; Ryu, H.; Lee, J.; Park, I. K.; Kim, Y. T.; Lee, Y. H.; Lee, H.; Hong, D. M.; Seo, J. H.; Bahk, J. H.; Jeon, Y.
Summary Lung resection surgery has been associated with numerous postoperative complications. Seventy‐eight patients scheduled for elective video‐assisted thoracoscopic lung resection were randomly assigned to receive standard postoperative care with incentive spirometry or standard care plus positive vibratory expiratory pressure treatment using the Acapella® device. There was no significant difference between incentive spirometry and the Acapella device in the primary outcome, forced expiratory volume in 1 s, on the third postoperative day, mean (SD) 53% (16%) vs 59% (18%) respectively, p = 0.113. Patients treated with both devices simultaneously found incentive spirometry to be less comfortable compared with the Acapella device, using a numeric rating scale from 1 to 5 with lower scores indicating higher comfort, median (IQR [range]) 3 (2–3 [2–4]) vs 1 (1–2 [1–3]) respectively, p < 0.001. In addition, 37/39 patients (95%) stated a clear preference for the Acapella device. Postoperative treatment with the Acapella device did not improve pulmonary function after thoracoscopic lung resection surgery compared with incentive spirometry, but it may be more comfortable to use.